ACTIVITY BASED COSTING SYSTEM : MODEL PENELUSURAN BIAYA OVERHEAD YANG AKURAT PADA UMKM SILK HOUSE SABBENA SOPPENG - Syamsu Alam (Pusat P2M Politeknik Negeri Batam, 2020)
This study aims to trace the absorption of overhead costs in the production process at Sabbena Soppeng's silk house, to identify appropriate cost drivers in allocating overhead costs to products that are accurate and do not occur distortion. This research uses descriptive method. Collecting data through interviews, observation, documentation. The analysis was carried out by applying a two-stage activity-based costing model. First, trace overhad costs to the “cost pool”. Second, trace the overhead costs to the product using multiple cost drivers. The results showed: a) the product category